Relationship between on- and out-degree of WWW - Liu, J; Dang, Y; Wang, Z; Zhou, T (2006)
In this paper, the relationship between the in-degree and out-degree of World-Wide Web is studies. At each time step, a new node with out-degree kout is added, where kout obeys the power-law distribution and its mean value is m. The analytical and simulation results suggest that the exponent of in-degree distribution would be ?i=2+1/m, depending on the average out-degree. This finding is supported by the empirical data, which has not been emphasized by the previous studies on directed networks.